2018
DOI: 10.1002/smj.2909
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of authority on peer motivation: Learning from Wikipedia

Abstract: Research Summary: We investigate the conditions under which authority can be deployed without reducing subordinate motivation. We show that lateral authority, the legitimacy to resolve task‐specific problems, is welcomed by members of an organization in the resolution of coordination conflicts, the more so (a) the fiercer the conflict to be resolved, (b) the higher the competence‐based status of the authority, (c) the lower the tenure of, and (d) the more focused the organizational members are. Analyzing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…In these communities, remotely located individuals are able to collaborate using digital technology that enables coordination through global visibility of coding work in progress as well as tools for managing dependencies and communication among contributors. Scholars have shown that in certain domains of the software industry, this form of organizing-an unambiguous offspring of the connectivity enabled by digitizationenables the aggregation of efforts from numerous contributors and provides credible alternatives to what for-profit firms do (e.g., Greenstein andZhu 2018, Klapper andReitzig 2018). The possibility of purely algorithmic solutions to the universal problems of organizing-for example, division of labor and integration of effort-appears to be at the verge of realization in these systems (Puranam et al 2014).…”
Section: Digital Transformation and The Internalmentioning
confidence: 99%
“…In these communities, remotely located individuals are able to collaborate using digital technology that enables coordination through global visibility of coding work in progress as well as tools for managing dependencies and communication among contributors. Scholars have shown that in certain domains of the software industry, this form of organizing-an unambiguous offspring of the connectivity enabled by digitizationenables the aggregation of efforts from numerous contributors and provides credible alternatives to what for-profit firms do (e.g., Greenstein andZhu 2018, Klapper andReitzig 2018). The possibility of purely algorithmic solutions to the universal problems of organizing-for example, division of labor and integration of effort-appears to be at the verge of realization in these systems (Puranam et al 2014).…”
Section: Digital Transformation and The Internalmentioning
confidence: 99%
“…Despite its limitations, our study contributes to the literature on community governance in general and dispute resolution in online communities in particular. It extends the understanding of dispute resolution in online communities from an operational one (Forte et al, 2009;Klapper & Reitzig, 2018) to a more strategic one. Our theory explains otherwise puzzling observations about OSS communities, such as the rare occurrence of governance disputes and the positive association between discussion group size and resolution.…”
Section: Discussionmentioning
confidence: 92%
“…Initiator characteristics Whether the initiator of the discussion was a project owner or not, and the amount of source code contributed by the initiator (contribution), could shape the amount of attention and support she receives from other participants. From prior research on operational disputes in online communities, we believe these variables may signify the competence-based status of the initiator (Dahlander & O'Mahony, 2011;Klapper & Reitzig, 2018). We obtained relevant information on the initiator's characteristics from the GitHub interface.…”
Section: Characteristics Of the Disputementioning
confidence: 99%
See 2 more Smart Citations